The Investigation of the Research on Out-of-School Learning Activities in Turkey: A Systematic Review - Mustafa Metin; Emir Oker; Aslı Saylan Kirmizigül (Universitas Pendidikan Indonesia, 2022)
This research aims to analyze the studies on out-of-school learning activities in Turkey between 2000 and 2020. For this purpose, 303 studies were selected, of which 211 articles, 73 master's thesis, and 19 doctoral dissertations, with the phrase